2021
DOI: 10.3389/fmicb.2021.618857
|View full text |Cite
|
Sign up to set email alerts
|

Multifaceted Mechanism of Amicoumacin A Inhibition of Bacterial Translation

Abstract: Amicoumacin A (Ami) halts bacterial growth by inhibiting the ribosome during translation. The Ami binding site locates in the vicinity of the E-site codon of mRNA. However, Ami does not clash with mRNA, rather stabilizes it, which is relatively unusual and implies a unique way of translation inhibition. In this work, we performed a kinetic and thermodynamic investigation of Ami influence on the main steps of polypeptide synthesis. We show that Ami reduces the rate of the functional canonical 70S initiation com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 57 publications
(121 reference statements)
0
12
0
Order By: Relevance
“…To compare the contribution of homologous and heterologous elongation factors EF-Tu, we decided to monitor a relatively late event of the A-site binding-tRNA accommodation-that would allow us to detect potential changes caused by heterologous EF-Tu during accommodation or preceding steps. The aa-tRNA accommodation in the A site changes the fluorescence intensity of the proflavin label (Prf) located at the elbow region of the initiator tRNA(Prf20) in the P site of the ribosome [23,24]. The interaction of both ternary complexes EF-Tu•GTP•Phe-tRNA Phe with the ribosome resulted in a fluorescence intensity decrease (Figure 1a).…”
Section: Kinetics Of Trna Interaction With the Ribosome Is Determined By The Properties Of Elongation Factor Ef-tumentioning
confidence: 99%
See 2 more Smart Citations
“…To compare the contribution of homologous and heterologous elongation factors EF-Tu, we decided to monitor a relatively late event of the A-site binding-tRNA accommodation-that would allow us to detect potential changes caused by heterologous EF-Tu during accommodation or preceding steps. The aa-tRNA accommodation in the A site changes the fluorescence intensity of the proflavin label (Prf) located at the elbow region of the initiator tRNA(Prf20) in the P site of the ribosome [23,24]. The interaction of both ternary complexes EF-Tu•GTP•Phe-tRNA Phe with the ribosome resulted in a fluorescence intensity decrease (Figure 1a).…”
Section: Kinetics Of Trna Interaction With the Ribosome Is Determined By The Properties Of Elongation Factor Ef-tumentioning
confidence: 99%
“…To study kinetics of A-site binding, initiation complex (0.05 µM) containing fMet-tRNA fMet (Prf20) (initiator tRNA labelled with proflavine at position 20 in the elbow region of tRNA) [23,24] was rapidly mixed with increasing concentration of ternary complex EF-Tu•GTP•Phe-tRNA Phe (0.1 µM, 0.2 µM, 0.4 µM, 0.8 µM, 1.2 µM, 2 µM) containing mesophilic or thermophilic EF-Tu. The reaction was monitored at 20 and 37 • C.…”
Section: Rapid Kineticsmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, amicoumacin A (36) ( Figure 10 ), produced by B. pumilus BN-103, inhibits B. subtilis 1779 with an MIC = 20.0 µg/mL. Further studies have shown that amicoumacin A inhibits the protein synthesis of methicillin-resistant Staphylococcus aureus by stabilizing the mRNA at the terminal E site on the ribosome during protein synthesis [ 107 ]. This disruption results in the perturbation of the membrane, leading to energy dissipation and eventual cell death [ 107 , 108 ].…”
Section: Antimicrobial Metabolites and Their Mechanism Of Actionmentioning
confidence: 99%
“…Further studies have shown that amicoumacin A inhibits the protein synthesis of methicillin-resistant Staphylococcus aureus by stabilizing the mRNA at the terminal E site on the ribosome during protein synthesis [ 107 ]. This disruption results in the perturbation of the membrane, leading to energy dissipation and eventual cell death [ 107 , 108 ]. Prumycin (37) ( Figure 10 ), isolated from a culture broth of B. amyloliquefaciens SD-32, exerts bactericidal and fungicidal effects, such as on S. sclerotiorum, with an MIC value of 1.56 µg/mL [ 109 , 110 , 111 ].…”
Section: Antimicrobial Metabolites and Their Mechanism Of Actionmentioning
confidence: 99%